Oral anticoagulation after catheter ablation of atrial fibrillation and the associated risk of thromboembolic events and intracranial hemorrhage: A systematic review and meta‐analysis. (18th July 2019) - Romero, Jorge; Cerrud‐Rodriguez, Roberto C.; Diaz, Juan C.; Rodriguez, Daniel; Arshad, Samiullah; Alviz, Isabella; Cerna, Luis; Rios, Saul; Monhanty, Sangamitra; Natale, Andrea; Garcia, Mario J.; Di Biase, Luigi
Abstract: Aims: We sought to examine whether continuing oral anticoagulation (OAC) after catheter ablation (CA) for atrial fibrillation (AF) is associated with improved outcomes. OAC reduces morbidity and mortality in patients with AF. However, the continuation of OAC following the blanking period of CA is controversial due to conflicting published data. Methods: A systematic review of Medline, Cochrane, and Embase was performed for studies comparing patients who were continued on OAC (ON‐OAC) vs those in which OAC was discontinued (OFF‐OAC). CHA2 DS2 VASc score had to be available for the classification of patients into high‐ or low‐risk cohorts (CHA2 DS2 VASc ≥ 2 and ≤ 1, respectively). The primary efficacy outcome was thromboembolic events (TE). Intracranial hemorrhage (ICH) was the primary safety outcome. Results: Five studies comprising 3956 patients were included (mean age, 61.1 ± 2.9 years; 72.4% male, CHA2 DS2 VASc ≤ 1 50.1%; CHA2 DS2 VASc ≥ 2 49.9%). After a mean follow‐up of 39.6 ± 11.7 months, OAC‐continuation was associated with a significant decrease in risk of TE in the high‐risk cohort (CHA2 DS2 VASc ≥ 2) (risk ratio [RR] 0.41, 95% confidence interval [CI] 0.21‐0.82, P = .01) with a RR reduction of 59%. ICH was significantly higher in the ON‐OAC group (RR, 5.78; 95% CI, 1.33‐25.08; P = .02). No significant benefit was observed in the low‐risk cohort ON‐OAC after the blanking period. Conclusion: Continuation of OAC after CA of AF with CHA2 DS2 VASc ≥ 2 is associated with a significant decreased TE risk and a favorable net clinical benefit in spite of ICH being significantly increased in the ON‐OAC group. Continued OAC offers no benefit with CHA2 DS2 VASC ≤ 1.